Determinants of Repurchase Intention on E-Grocery Alfagift - Elistia Elistia; Resty Emerellia Septiani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2023)
The rapid development of technology affects people's online shopping activities through e-grocery applications, which are widely used because they provide convenience for customers. Repurchase intention is one of the most important things because it will show repurchase if the customer is satisfied with the product and service received. This study analyses the influence of customer trust, customer satisfaction, engagement, and repurchase intention. This type of research is descriptive causality with a quantitative approach through a purposive sampling technique with 207 Alfagift e-grocery customer respondents in the Tangerang City area—primary data analysis using the Structural Equation Model. The results of this study indicate that customer trust can increase customer satisfaction and engagement. Furthermore, customer satisfaction and engagement can increase repurchase intention. However, customer trust does not affect repurchase intention. Customer trust is the factor that has the most substantial impact on customer satisfaction. The most decisive impact on increasing repurchase intention is customer engagement, compared to customer satisfaction. However, customer trust has yet to be able to impact repurchase intention positively. Therefore, it is necessary to carry out a strategy to maintain and increase customer trust to impact repurchase intention in Alfagift e-grocery significantly.